Internal solitary waves on the NW African shelf: A heuristic approach to localize diapycnal mixing hotspots. (1st September 2021) - Gentil, Mathieu; Floc'h, France; Meunier, Thomas; Ruiz-Angulo, Angel; Roudaut, Gildas; Perrot, Yannick; Lebourges-Dhaussy, Anne
Abstract: Turbulent mixing on continental shelves plays roles in the structure and dynamics of marine ecosystems, nutrient cycling, primary production and dispersion of pollutants. Describing and understanding internal wave dynamics enables improved mapping of mixing over continental shelves, especially in complex environments where many processes may interact, such as in upwelling systems. This paper describes internal wave propagation and dissipation in the Moroccan upwelling system using a comprehensive set of hydrographic observations made during two in situ surveys. The acoustic backscatter of the echosounder is shown to be a rapid and convenient survey tool for detecting internal solitary waves (ISWs) on large spatial scales, through the high-frequency oscillation of the zooplankton layer during nighttime conditions. Along ISW trains, enhanced diapycnal mixing episodes are observed with increased dissipation coefficients in the thermocline (O(10 -7 W kg -1 )), associated with overturning up to 6 m. Mixing due to internal wave soliton packets shows large spatial and temporal variability, but contributes to the overall mixing processes and is responsible for large intermittent variations in the thermocline position. The joint use of a multifrequency echosounder and a current profiler ADCP allows mixing to be quantified (via the Richardson number) on large spatial scales. Validation and use of this method in other coastal regions could be useful to determine regional mixing parameterization in numerical models. Highlights: Internal solitary waves (ISWs) are ubiquitous over the Moroccan shelf. ISWs increase Thorpe displacements and dissipation rates in the water column. ISWs contribute to the overall mixing processes. An echosounder is used as a proxy of stratification to derive the Richardson number.